A redescription of the Mediterranean endemic cladoceran Daphnia chevreuxi Richard, 1896 (Cladocera: Daphniidae) - Kotov, Alexey A.; Garibian, Petr G.; Neretina, Anna N.; Marrone, Federico (Zootaxa, 2022)
The Mediterranean area is a biodiversity and endemism hotspot. “Circum-Mediterranean” taxa are known among different hydrobionts, including the water fleas. Some Mediterranean endemic cladoceran taxa have been described or redescribed according to modern taxonomical standards, but accurate drawings are missing for others. Here we redescribe the Mediterranean endemic Daphnia chevreuxi Richard, 1896 (Crustacea: Cladocera) and briefly review available data on its distribution and ecology. The species is confirmed to be a typical inhabitant of the temporary ponds of the central Mediterranean area, whereas its populations from the eastern Balkans and the Middle East should be studied in order to check for their actual identity. We conclude that the Mediterranean area is an example of a well-studied region as Cladocera are concerned, but the study of other regions is necessary in order to understand better the cladoceran diversity and distribution patterns in Eurasia.